2015
DOI: 10.1039/c5cp02486b
|View full text |Cite
|
Sign up to set email alerts
|

High coverage adsorption and co-adsorption of CO and H2 on Ru(0001) from DFT and thermodynamics

Abstract: The adsorption and co-adsorption of CO and H2 at different coverages on p(4 × 4) Ru(0001) have been computed using periodic density functional theory (GGA-RPBE) and atomistic thermodynamics. Only molecular CO adsorption is possible and the saturation coverage is 0.75 ML (nCO = 12) with CO molecules co-adsorbed at different sites and has a hexagonal adsorption pattern as found by low energy electron diffraction. Only dissociative H2 adsorption is possible and the saturation coverage is 1 ML (nH = 16) with H ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 66 publications
(137 reference statements)
7
31
1
Order By: Relevance
“…The contribution of vibrations to the solid surface is negligible and can be substituted by the results from DFT. 52 The gas phase term can be calculated by the equation (2):…”
Section: Thermodynamicsmentioning
confidence: 99%
“…The contribution of vibrations to the solid surface is negligible and can be substituted by the results from DFT. 52 The gas phase term can be calculated by the equation (2):…”
Section: Thermodynamicsmentioning
confidence: 99%
“…[19][20][21][22][23] For example, the ordered structures of CO on Co (0001), Ru(0001) and Pt (111) surfaces can be tuned by lateral interactions under different coverages. [24][25][26] In addition, the NO adsorption has been studied with both experiment and theoretical techniques on the TiO 2 (110) surface, the results found that N 2 O molecules as reduction product desorbed at 250 K. [27] The formation of N 2 O was observed to increase with NO coverage at 110 K, indicating that coverage effects play a role. [28] Theoretical calculations also demonstrated that the halfmonolayer coverage of NO on the TiO 2 (110) is in agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Surface phase diagrams are widely used to study the most stable surface composition as a function of reaction conditions. [25,26,31] For the low-coverage surface configurations of metals, full DFT calculations are relatively computationally inexpensive and are commonly used to identify the stability of a species on the surface. In addition, linear scaling relations driven by the d-band model have been established for adsorbates at low-coverage on metal surfaces, where the slope of the scaling relations follows simple bond counting principles.…”
Section: Introductionmentioning
confidence: 99%
“…While metallic ruthenium is known to catalyze the reverse water gas shift reaction, its interaction with CO 2 has not, to our knowledge, been the subject of investigation. 58 The chemisorption and reaction of CO 2 on metal oxides, including RuO 2 , and metallic alloys, including Ru, are well-studied processes. 1,3 Moreover, the adsorption of CO 2 on other single-crystal metal surfaces has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%